Centaurea ibn-tattoui (Asteraceae), a new narrow endemic species from north-eastern Morocco - Chambouleyron, Mathieu; Bidat, Matthieu; Léger, Jean-François (Phytotaxa, 2014)
Centaurea ibn-tattoui is described and illustrated as a new species from north-eastern Morocco. Intermediate involucral bracts and leaves are the discriminant features separating it from other closely related taxa of C. sect. Acrocentron.